How to capitalize the tribe - the Toyota Prius case study - Silva, Susana Costa e (2016)
Purpose: This paper attempts to extend the emergent literature on consumer tribes, in order to provide firms with a more complete understanding of this phenomenon. The main purpose of the study is to identify the existence of tribal behaviour, as well as to propose a model that could guide brands in the identification of tribal bonds. Design/methodology/approach: This study comprises an examination of tribes’ growing power and influence on consumers’ behaviour. The research is approached interpretively with a case-study investigation of the Prius (Toyota’s hybrid car) tribe. Findings: Four different levels of involvement in a consumer-brand relation are proposed, “tribal” being the most desirable level for a brand to achieve. We also suggest some ways for firms to develop their tribes, and to benefit from that relation. Research limitations/implications: One tribe was examined in this case study. Future research should apply to other case contexts. Levels of tribal affection should also be approached in other investigations, in a way that enables future representativeness and replication. Practical implications: These findings provide direction for firms to be aware of the crucial power of tribes and its relevance in today’s market context. This may empower firms to understand this growing force and integrate it within their marketing activities. Originality/value: The originality of this paper resides in the systematisation of levels of affection in consumer-brand relation, which culminate in the tribal stage. Ways in which companies may support tribes are also suggested. The proposed model aims to be a guide for firms in the identification of tribal bonds and, consequently, in the improvement of the relation between the firm and the tribe.